Performance of a 7-Type HPV mRNA Test in Triage of HPV DNA Primary Screen Positive Women Compared to Liquid-Based Cytology - Sveinung Wergeland Sørbye; Bente Marie Falang; Mona Antonsen (Journal of Molecular Pathology, 2023)
Background: A plethora of data supports HPV-based screening to be the preferred strategy for cervical cancer prevention. The shift to a more sensitive first-line test brings the need of effective triage up for discussion. Currently, most algorithms apply cytology as a triage of HPV-DNA positive women. This study compared the performance of a 7-type HPV-mRNA test to cytology. Methods: From 1 January 2019 until 31 December 2021, cervical samples from 58,029 women were examined at the University Hospital of North Norway. A total of 30.5% (17,684/58,029) fulfilled the criteria for HPV-DNA primary screening. All positive samples were triaged by cytology and followed-up according to national guidelines through 2022. Additionally, a 7-type HPV-mRNA test was applied. The study endpoint was a histologically confirmed high-grade lesion (CIN2+). Results: A total of 5.6% (990/17,684) had positive HPV-DNA test, 97.2% (962/990) with valid HPV-mRNA results. A total of 55.5% (534/962) had abnormal cytology (ASC-US+), and 35.1% (338/962) had a positive HPV-mRNA test. A total of 13.9% (134/962) had CIN2+. The sensitivity (CIN2+) of cytology versus the HPV-mRNA test was 76.1% (102/134) versus 73.1% (98/134), p = 0.67. The specificity was 47.8% (396/828) versus 71.0% (588/624), p < 0.001. PPV was 19.1% (102/534) and 29.0% (98/338), p < 0.001, respectively. The number of colposcopies per CIN2+ detected by cytology and HPV-mRNA test was 5.2 and 3.1. Conclusion: The 7-type HPV mRNA test was significantly more specific than cervical cytology in a triage of HPV-DNA positive women. Using this biomarker as the threshold for colposcopy may better balance the benefits and harms of screening.